Pengaruh Ketimpangan Pendapatan Suami Istri Terhadap Tingginya Kasus Cerai Gugat Di Pengadilan Agama Kelas 1B Kabupaten Ponorogo - Arlinta Prasetian Dewi; Budi Setiawan (MAHAKIM Journal of Islamic Family Law, 2019)
Ponorogo is a city that has a high rate of divorce cases. From the divorce cases, the majority of submissions come from female workers who work as migrant workers, the implication is that the wife has a far greater income than her husband giving rise to a shift in the role of husband and wife which also results in a shift in rights and obligations. Although Islam allows a wife to work (in the context of helping her husband), it is expected that the husband and wife have considered together the good and bad consequences that may arise from the decision. Income gap or income inequality between husband and wife if not interpreted wisely can have an impact on the disharmony of the relationship between the two can even reach the stage of divorce. This research will explain an analyze the effect of income inequality between husbnad and wife on the high cases of divorce in Ponorogo. For that, researcher will examine this income inequality in the view of the sociology of Islamic law in the Ponorogo community in particular and driving factors the rise of female workers in Ponorogo and things that arise when the wife’s income is greater than her husband. The paradigm of this research is used a qualitative paradigm with emphasis on case studies in teh field. The result of the research stated that income inequality where the wife has a greater income than the husband is not a main problem in divorce cases, but there are other factors as a trigger such as the inability of the husband in managing finances, the wife’s takings is only for consumptive activities and even tends to spree, the interference from the husband’s family, especially in financial matters, lack of understanding of religion, and infidelity. This hiigh financial ability of the wife ultimately makes the wife dare to sue for divorce of her husband.